A founder EIF2AK4 mutation causes an aggressive form of pulmonary arterial hypertension in Iberian Gypsies. (7th January 2015) - Tenorio, J.; Navas, P.; Barrios, E.; Fernández, L.; Nevado, J.; Quezada, C.A.; López‐Meseguer, M.; Arias, P.; Mena, R.; Lobo, J.L.; Alvarez, C.; Heath, K.; et al.
Abstract : Pulmonary arterial hypertension (PAH) is a pathological condition characterized by a persistent and progressive elevation of pulmonary vascular resistance with devastating consequences if untreated. In the past recent years, several genes have been related to PAH, however, the molecular defect remains unknown in a significant proportion of patients with familial PAH (∼20%). During the past few years, we have observed that PAH shows a particular behavior in Iberian Gypsies, with more aggressive course and frequently affecting multiple members of the same family. We studied five Gypsy families in whom at least one individual from each family developed a severe form of PAH and in whom no mutation had been identified in the common genes. We applied SNP‐array‐based homozygosity mapping in three families and obtained, among others, one of which included the gene EIF2AK4, recently reported in patients with PAH from group‐1' pulmonary veno‐occlusive disease (PVOD) and pulmonary capillary hemangiomatosis (PCH). Subsequently, we sequenced EIF2AK4 and found a homozygous mutation in all five families: c.3344C>T(p.P1115L). The majority of our patients required early lung transplantation. Hence, this mutation appeared with a more severe phenotype than previously reported for other EIF2AK4 mutations. The finding of this novel mutation is important for genetic counseling and calculation of population recurrence risks.